Text in Context (KULT_online, 2009)
This anthology aims to contextualise literature by using the theoretical framework of cultural studies. To this end, such key concepts as ‘cultural knowledge’ and ‘intertextuality’ (which make up the volume’s title), as well as ‘performance’ and ‘writing back’ are defined, discussed and thoroughly exemplified. The volume is much like a textbook for students as well as for established scholars who are not captive to a strictly text-oriented hermeneutics.